Las voces de los docentes: motivos de elección de la carrera docente, valores subyacentes - Pidello, María Amelia; Rossi, Beatriz; Sagaztizabal, María de los Ángeles (Pontificia Universidad Católica del Perú. Fondo Editorial, 2013)
This paper analyzes, from the views expressed by teachers in activity, the motivations that led and lead them to uphold the performance of the teaching task. This problem is systematically surveyed in the framework of the project Observatory of the conceptions of teachers and future teachers about the school, teacher training and students (Irice/Conicet, OIE/Unesco). The comprehension of the senses and meanings that guide the choice of teaching implied, by the subjects questioned, a reflection on the constitutive aspects of the teaching role and a travel through the spaces of confluence of processes and representations. This study allowed us to recognize the prevailing needs in such choice of career, as well as the understanding of its significance and the values that guide it.

En este artículo se analiza, a partir de lo expresado por enseñantes en actividad, lasmotivaciones que condujeron y llevan a sostener el desempeño de la tarea docente. Esta problemática es sistemáticamente relevada en el marco del Observatorio de las concepciones de los docentes y futuros docentes acerca de la institución educativa, laformación docente y los alumnos (Irice/Conicet, OIE/Unesco). La comprensión de los sentidos y significados que guían la elección de la docencia implicó, por parte de los sujetos interpelados, una reflexión sobre los aspectos constitutivos del rol y un recorrido por los espacios de confluencia de procesos y representaciones. Este estudio posibilitó nuestro reconocimiento de las necesidades prevalecientes en dicha elección, como así también la interpretación de su entramado y la comprensión de los valores que la orientan.
The voices of teachers: reasons for choosing the teaching profession, underlying values
Keywords: Motivos; Carrera Docente; Valores; Motivation; Teaching Profession; Values; https://purl.org/pe-repo/ocde/ford#5.03.00